If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -6x + 6x + 12 = 12x + -24 Reorder the terms: 3 + 12 + -6x + 6x = 12x + -24 Combine like terms: 3 + 12 = 15 15 + -6x + 6x = 12x + -24 Combine like terms: -6x + 6x = 0 15 + 0 = 12x + -24 15 = 12x + -24 Reorder the terms: 15 = -24 + 12x Solving 15 = -24 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 15 + -12x = -24 + 12x + -12x Combine like terms: 12x + -12x = 0 15 + -12x = -24 + 0 15 + -12x = -24 Add '-15' to each side of the equation. 15 + -15 + -12x = -24 + -15 Combine like terms: 15 + -15 = 0 0 + -12x = -24 + -15 -12x = -24 + -15 Combine like terms: -24 + -15 = -39 -12x = -39 Divide each side by '-12'. x = 3.25 Simplifying x = 3.25
| (-4)+x=(-7) | | .83v+10=5 | | (-8-3)3-(4-6-2)= | | 17615+550p=74815 | | 3x-25=2x+2 | | -8x+4(x+2x-8)=-12 | | 0.4(x-3.5)=5.8x+1.84 | | 5/2a-5=30 | | 3x^8+30x^7+48x^6=0 | | (5-11i)-(-7+5i)= | | 75*60=95*40x | | .5w+5=13 | | (-3)=(-5)-x | | 2x-2[8(x+4)-(x-4)]-2= | | 8h-13-h=4-27h-2 | | 7-12x-5-2x=4 | | 93.96=4.7*p+8.7*p-2.6*p | | (-3)(14)(1.8)= | | 17615+550p=0 | | -42x^2-57x+120=0 | | 6-8(n-5)=6(-8n+2)-6 | | .75k+9=6 | | 11=[m+7] | | (81)^3/4 | | (-4)-x=6 | | (81)^(-3/4) | | 93.96=4.7*p+8.7*p-.6*p | | 3x+6-2x+8=24 | | 4/s–3=-2/5 | | (2x-3)-2(-x+4)=4x-11 | | 4/3y-16=-40 | | N*0.2=25 |